2002
DOI: 10.1111/j.1582-4934.2002.tb00459.x
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo differentiation of umbilical cord blood progenitor cells in the presence of placental conditioned medium

Abstract: Hematopoetic stem cells (HSC) are the progenitors for the lympho‐hematopoietic system, with long lifespan and high proliferation potential. Transplantation of HSC from bone marrow or peripheral blood represents a standard therapy in severe hematological conditions. A possible alternative source of HSC is the umbilical cord blood, prepared by various separation procedures followed by expansion in cultures supplemented with hematopoietic growth factors. In order to check the effects of placental conditioned medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Several studies have reported that conditioned medium (CM) obtained from MSCs contains putative growth factors that accelerate cell division, delay senescence, and enhance cell differentiation (Hakkinen et al. , 2001; Chivu et al. , 2002; Elder, 2002; Torres et al.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have reported that conditioned medium (CM) obtained from MSCs contains putative growth factors that accelerate cell division, delay senescence, and enhance cell differentiation (Hakkinen et al. , 2001; Chivu et al. , 2002; Elder, 2002; Torres et al.…”
Section: Resultsmentioning
confidence: 99%
“…Several features of our experimental design may account for these differences. We supplemented the hADAS cell clones with conditioned media containing putative growth factors which may accelerate cell division, delay senescence, and enhance cell differentiation (Hakkinen et al, 2001;Chivu et al, 2002;Elder, 2002;Torres et al, 2002). Furthermore, our hADAS cell cloning was conducted on low adhesion suspension dishes; adhesion has been found to influence the growth and differentiation potential of stem cells derived from skeletal muscle (Huard et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…A second growth cocktail was based on 20% placental conditioned medium (PCM) (obtained as described before - [14]) and 2% autologous plasma. After three days, total numbers of nucleated and viable cells were determined using trypan blue exclusion test.…”
Section: Expansion Culturesmentioning
confidence: 99%